2000
DOI: 10.1007/s11664-000-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Copper substrate dissolution in eutectic Sn-Ag solder and its effect on microstructure

Abstract: The dissolution of Cu into molten Sn-3.8at.%Ag (Sn-3.5wt.%Ag) solder and its effect on microstructure were studied by light microscopy, scanning microscopy, and x-ray microanalysis. X-ray microanalysis of the average Cu content of samples soldered under various conditions showed that the amount of Cu dissolved during soldering increased with increasing soldering temperature and time and that the rate of dissolution could be described by a Nernst-Brunner equation. Microstructurally it was found that the volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 4 publications
5
72
0
Order By: Relevance
“…The values for the SnAg and SnCu alloys are consistent with those reported previously for IMC layer growth for eutectic Sn-Ag solder. 11,12) (2) Initial stage of intermetallic growth on Cu substrate As shown above, some IMC thickness values, notably those for short and long holding times, deviate from the least square fitted average growth line. The deviations are indeed the greatest on a percentage basis at short and long times and they are the greatest for the lower temperatures.…”
Section: )mentioning
confidence: 99%
“…The values for the SnAg and SnCu alloys are consistent with those reported previously for IMC layer growth for eutectic Sn-Ag solder. 11,12) (2) Initial stage of intermetallic growth on Cu substrate As shown above, some IMC thickness values, notably those for short and long holding times, deviate from the least square fitted average growth line. The deviations are indeed the greatest on a percentage basis at short and long times and they are the greatest for the lower temperatures.…”
Section: )mentioning
confidence: 99%
“…Primary Cu6Sn5 has been reported to grow with various morphologies such as needles [10][11][12], hollow rods [11,13], X-shapes [9,14,15], Y-shapes [8,9], H-and M-shapes [16,17] and as dendrites [6,18]. Since many of these studies have been based on arbitrary 2D cross sections, it is not clear how many of these morphologies are separate growth forms in 3D.…”
Section: Introductionmentioning
confidence: 99%
“…30,31) It is caused by that Ag promotes the formation of the Cu 6 Sn 5 layer because Ag increases the solubility of Cu in Sn. 32) The Ag 3 Sn IMC forms at the solder alloy/Cu interface when the Ag content in solder alloy is above 0.1 mass% as reported by Huh et al 33) From the XRD pattern, the Ag 3 Sn is found at the Sn-9Zn-0.5Ag/Cu interface because the Ag content in the solder alloy is higher than 0.1 mass%.…”
Section: Thermal Properties Of the Solder Alloysmentioning
confidence: 70%